Poor adherence to iron-folic acid supplementation and associated factors among pregnant women who had at least four antenatal care in Ethiopia. A community-based cross-sectional study - Asmamaw, Desale Bihonegn; Debebe Negash, Wubshet; Bitew, Desalegn Anmut; Belachew, Tadele Biresaw (Frontiers in Nutrition, 2022)
Background In developing countries, including Ethiopia, maternal mortality is a major public health concern. The Ethiopian Demographic Health Survey (EDHS) reported that the maternal mortality ratio (MMR) was 420 per 100,000 live births in 2016. Iron-folic acid supplementation (IFAS) is a key intervention to reduce these deaths. Therefore, this study aimed to assess the magnitude of poor adherence to IFAS and associated factors among pregnant women who had at least four antenatal care in Ethiopia. Methods Secondary data analysis was used using 2016 Ethiopian Demographic and Health Survey (EDHS). We analyzed the data using Stata version 14. To identify factors associated with poor adherence to IFAS, a multilevel mixed-effect logistic regression model was fitted. Variables with a p < 0.05 in the multilevel mixed-effect logistic regression model were declared as significant factors associated with poor adherence to IFAS. Result The magnitude of poor adherence to IFAS was 82.87% (95% CI: 80.96–84.65). Women education; primary [adjusted odds ratio (AOR) = 0.48; 95% CI: 0.31–0.75] and secondary (AOR = 0.52; 95% CI: 0.29–0.96), husband education; primary (AOR = 0.56; 95% CI: 0.36–0.86) and secondary (AOR = 0.51; 95% CI: 0.29–0.95), and community media exposure (AOR = 0.47; 95% CI: 0.27–0.79) were significantly associated with poor adherence to IFAS. Conclusion In the current study, more than eight out of ten pregnant women who had at least four antenatal care had poor adherence to IFAS. Thus, promoting maternal and husband education and establishing community media with a priority on iron-folic acid supplementation and health-related programs are essential strategies to reduce poor adherence to IFAS.